Avaliação da mancha de ramulária em três safras no Mato Grosso e sua influência na produção e qualidade de fibra do algodoeiro - Moura, Joyce Dorneles (2016)
Mato Grosso is the Brazilian state responsible for the largest planted area and greatest productivity of cotton seed and fiber in the country. Although Mato Grosso has the best fertility areas of the country and favorable weather conditions for cotton development and production, some pests, atypical climatic conditions and diseases, such as Ramularia, have contributed to the decrease of yield and planted area. Breeding programs are the best way, in the long term, to solve these problems. In addition to resistance to disease, improving performance in terms of yield and fiber quality, and adaptability of the germplasm to the region are very important. Ramularia was considered a secondary disease until 2007; however, with the advent of other varieties resistant to diseases that were previously primary ones - Ramulose, for example – a decreased need for fungicide application occurred and, furthermore, the migration of the crop to other states besides São Paulo and Paraná, with more favorable conditions for disease, it began to bother producers and interfere negatively on productivity. This study analyzed the behavior of three commercial cotton varieties in relation to the severity caused by Ramularia during 3 crops in Mato Grosso state: seasons 2011-12, 2013-14 and 2014-15, and its influence on production, yield and fiber quality. Three commercial cotton varieties, DeltaOpal, FM993 and FMT705, were tested in three farms located in Campo Verde, Sapezal and Primavera do Leste. The evaluations to quantify Ramularia were performed approximately 100 days after emergence. A sample of 30 bolls was used to perform tests of lint percent, fiber quality, and the production per plot was quantified through weighing plot production. According to results observed, the 2011-12 season - historically presented the best weather, benefiting both the culture and the disease - was the one with the greatest cotton production values and also the greatest severity values for Ramularia. The values of lint percent and fiber showed some differences among cultivars and locations, but still remained within acceptable market values. Regarding the response to the disease, it was observed during the three seasons a stable behavior of the tested varieties, FMT705 performed as the most resistant, while DeltaOPAL was the most susceptible to Ramularia.